Optical and electronic properties of Cu-Mn solid solutions - Bondar, V.M.; Stashchuk, V.S.; Polianska, O.P.; Chernukha, Ie.O.; Tsuk, B.A.; Lysiuk, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The optical properties of Cu-Mn alloys with Mn concentrations of 2, 5, 10 and
17.5% (which corresponds to the γ-solid solutions) were studied within a wide spectral
range of 0.23 to 2.8 μm (0.44…5.39 eV). Real and imaginary parts of the refractive index
were measured, other optical properties such as dielectric constant, optical conductivity
and the coefficient of specular reflectance at normal incidence were calculated being
based on them. The analysis of the dispersion dependences ε(hν), R(hν) and σ(hν)
enabled us to offer the electronic structure model for these alloys. According to this
model, the electronic spectra (dependence of the density of electronic states on energy
N(E)) of alloys with the indicated concentrations of components are the superposition of
electronic spectra of Cu host, with weights equal to Cu concentrations, and the density of
states within the impurity band, calculated using the experimental data.
Remove selected